Evaluation of Urban Improvement on the Islands of the Venice Lagoon: A Spatially-Distributed Hedonic-Hierarchical Approach - Anita Fassio; Margaretha Breil; Carlo Giupponi; Paolo Rosato (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper presents a model for the evaluation of environmental and urban improvements on the islands of the Venetian lagoon. The model simulates the changes in residential real estate values using a value function integrated in a geographical database which provides spatial distributions of values changes. The fairly weak market signals, fragmented demand and strong externalities, and the scarcity of market data available do not permit the use of econometric models for value appraisal. Appropriate hedonic-hierarchical value functions are calibrated on the basis of a set of indicators of the characteristics of the buildings and the location. Some applications of the model are illustrated simulating two scenarios of future interventions which are actually being discussed or realised and involving the island of Murano, Burano and S. Erasmo in the Venice Lagoon. The interventions considered are: subway beyond the lagoon connecting Murano with Venice and the mainland, and the solution of high water problems on Murano, Burano and S. Erasmo.
Keywords: R21; R31; 330; Public work assessment; Property value; Hierarchical analysis